Improving Teacher Competence Through Digital-Based Learning Innovation Workshop at MAS Tarbiyah Islamiyah Hamparan Perak, Deli Serdang Regency - Tumiran; Bahtiar Siregar; Nanda Rahayu Agustia; Faiza Azhari (Pascasarjana Universitas Mataram, 2025)
This community service aims to improve teacher competence in integrating digital technology in the learning process at MAS Tarbiyah Islamiyah Hamparan Perak, Deli Serdang Regency. Activities are carried out through a workshop method that focuses on digital-based learning innovations, including the use of digital platforms, interactive media, and effective modern learning strategies. The activity participants consisted of MAS Tarbiyah Islamiyah teachers who have been facing various obstacles in implementing digital learning optimally. The results of the service showed that the workshop succeeded in increasing teachers' understanding and skills in applying various digital tools and platforms in learning. In addition, the teachers also showed high enthusiasm and motivation to continue developing learning innovations. This activity is expected to improve the quality of learning and support the creation of a more interactive and enjoyable learning environment for students.